Osteogenic cell differentiation on H-terminated and O-terminated nanocrystalline diamond films - Liskova, Jana; Babchenko, Oleg; Varga, Marian; Kromka, Alexander; Hadraba, Daniel; Svindrych, Zdenek; Burdikova, Zuzana; Bacakova, Lucie (International journal of nanomedicine, 2015)
Nanocrystalline diamond (NCD) films are promising materials for bone implant coatings because of their biocompatibility, chemical resistance, and mechanical hardness. Moreover, NCD wettability can be tailored by grafting specific atoms. The NCD films used in this study were grown on silicon substrates by microwave plasma-enhanced chemical vapor deposition and grafted by hydrogen atoms (H-termination) or oxygen atoms (O-termination). Human osteoblast-like Saos-2 cells were used for biological studies on H-terminated and O-terminated NCD films. The adhesion, growth, and subsequent differentiation of the osteoblasts on NCD films were examined, and the extracellular matrix production and composition were quantified. The osteoblasts that had been cultivated on the O-terminated NCD films exhibited a higher growth rate than those grown on the H-terminated NCD films. The mature collagen fibers were detected in Saos-2 cells on both the H-terminated and O-terminated NCD films; however, the quantity of total collagen in the extracellular matrix was higher on the O-terminated NCD films, as were the amounts of calcium deposition and alkaline phosphatase activity. Nevertheless, the expression of genes for osteogenic markers - type I collagen, alkaline phosphatase, and osteocalcin - was either comparable on the H-terminated and O-terminated films or even lower on the O-terminated films. In conclusion, the higher wettability of the O-terminated NCD films is promising for adhesion and growth of osteoblasts. In addition, the O-terminated surface also seems to support the deposition of extracellular matrix proteins and extracellular matrix mineralization, and this is promising for better osteoconductivity of potential bone implant coatings.
Keywords: Tissue Engineering; Collagen Type I; Calcium; Saos-2; kvantitativní polymerázová řetězová reakce; Diamond; Cell Proliferation; Fluorescent Antibody Technique; fluorescenční protilátková technika; osteoblasty; vápník; Alkaline Phosphatase; kolagen typu I; Spectrum Analysis, Raman; Ramanova spektroskopie; buněčná diferenciace; Osteoblasts; alkalická fosfatasa; nanocrystalline diamond film; osteoblast; Microscopy, Atomic Force; diamant; Real-Time Polymerase Chain Reaction; extracelulární matrix; mikroskopie atomárních sil; tkáňové inženýrství; Wettability; collagen; lidé; smáčivost; Microscopy, Electron, Scanning; Humans; SHG; Extracellular Matrix; proliferace buněk; mikroskopie elektronová rastrovací; Cell Differentiation